A scintillation detector configuration for pulse shape analysis - Phan, Văn Chuân (Elsevier Korea LLC, 2023)
This paper presents a neutron detector configuration using EJ-301 scintillation liquid, a R9420 photo-multiplier and a homemade preamplifier. The detector qualities which include the energy linearity, efficiency response and neutron/gamma discrimination are guaranteed for neutron detection in the energy range from 0 to 3000 keVee. Regarding the neutron/gamma discrimination capability, four pulse shape discrimination (PSD) methods which are the threshold crossing time (TCT), pulse gradient analysis (PGA), charge comparison (CC) and correlation pattern recognition (CPR), were evaluated and discussed; among of these, the CPR method provides the best neutron/gamma discrimination.